NITROGENOUS FERTILIZATION LEVELS AND ROOT MYCORRHIZAL COLONIZATION ON PLANT GROWTH AND PRODUCTIVITY IN WHEAT CROPS - Singh, Basant Narain (The Scientific Temper, 2018)
In a two-year study (2002-2003), mycorrhizal treatments in conjunction with three nitrogen fertilization levels of 0, 50, 100 kg of N/ha were tested on durum wheat in continuous cropping. The study took place in the Province of Foggia, a semi-arid area of the Mediterranean Basin in southern Italy, with silty-clay soil classified as Typic Chromoxerert. Seeds of cultivar Simeto were inoculated at sowing, and a completely randomized block design with three replications with and without inoculation was adopted. Plant samples were taken during the vegetative cycle of the durum wheat, and the root mycorrhizal colonization was examined. In all treatments, the percentage of colonised root length was significantly higher in the inoculated plants than it was in the control. The plants inoculated and fertilized with 50 kg N/ha showed a significant increase in grain yield.